Handbook of Child Psychology and Developmental Science 2015
DOI: 10.1002/9781118963418.childpsy104
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Development of Thinking, Feeling, and Acting

Abstract: Models of psychological development have taken a relational turn. From this view, human psychological development is an integrative, dynamic, emergent, and coactive process. It is integrative in the sense that psychological processes never operate in isolation of each other. There is no such thing as a purely cognitive, emotional, or behavioral act. Any given instance of psychological activity necessarily involves the structured integration of multiple component psychological systems. Despite their organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 186 publications
1
61
0
3
Order By: Relevance
“…Professor Perlman (2015) observes that the emphasis on RDS metatheory may herald the end of a focus on grand theories of human development (e.g., Piaget, 1970). We agree and, in turn, we would point out that RDS metatheory provides "design criteria" for more content-specific models of developmental processes, for example, as may be involved in positive human development (e.g., , thinking, feeling, and skill development (Mascolo & Fischer, 2015), moral development (Turiel, 2015), and agency (Sokol, Hammond, Kuebli, & Sweetman, 2015). Thus, in a "developmental science funnel," that has at its wide end paradigmatic and metatheoretical constructs, and at its narrow end theory-derived and methodologically rigorous data, the models associated with RDS metatheory constitute midrange theories.…”
Section: Professor Perlman's Commentsmentioning
confidence: 80%
“…Professor Perlman (2015) observes that the emphasis on RDS metatheory may herald the end of a focus on grand theories of human development (e.g., Piaget, 1970). We agree and, in turn, we would point out that RDS metatheory provides "design criteria" for more content-specific models of developmental processes, for example, as may be involved in positive human development (e.g., , thinking, feeling, and skill development (Mascolo & Fischer, 2015), moral development (Turiel, 2015), and agency (Sokol, Hammond, Kuebli, & Sweetman, 2015). Thus, in a "developmental science funnel," that has at its wide end paradigmatic and metatheoretical constructs, and at its narrow end theory-derived and methodologically rigorous data, the models associated with RDS metatheory constitute midrange theories.…”
Section: Professor Perlman's Commentsmentioning
confidence: 80%
“…A second, alternate view is based on functionalist theories of emotion that emphasize emotions as critical to motivating goal-directed behavior (Magai & McFadden, 1995;Saarni, Mumme, & Campos, 1998). Consistent with this viewpoint, dynamic coactions of emotion and cognition generate and organize individuals' behaviors during social interactions (Mascolo & Fischer, 2015). Specifically, individuals continually appraise how well their concerns are met and attribute why concern-promoting or violating events occur.…”
Section: Ei As a Moderatormentioning
confidence: 99%
“…Second, we assessed study children's EI as reported by teachers at Grade 4 as a moderator of the associations between study children's attribution biases and child-friend interaction quality. Based on prior theoretical (e.g., Frijda, 1986;Lemerise & Arsenio, 2000;Mascolo & Fischer, 2015) and empirical (e.g., Burgess et al, 2006;Laible et al, 2014;Orobio de Castro et al, 2002;Runions & Keating, 2010) work, we hypothesized that (a) study children's more hostile versus benign attribution bias would be associated with higher levels of negative childfriend interaction and lower levels of positive child-friend interaction, and (b) EI would moderate these associations, such that they would be stronger among study children who had higher levels of EI.…”
Section: The Current Studymentioning
confidence: 99%
“…Při samotném výzkumu se zaměřujeme především na projevy tacitních znalostí v oblasti myšlení, přesto v definici uvádíme také další typy projevů tak, aby byla co nejkomplexnější. Oblasti jednání a prožívání považujeme za neoddělitelně provázané s kognicí (Mascolo & Fischer, 2010), protože mentální procesy jsou utvářeny nejen "procesy v mozku, ale i jejich kombinací s širší tělesnou strukturou (se senzomotorickým systémem)" (Rowlands, 2010, s. 53).…”
Section: Definice Tacitní Znalostiunclassified